Microscopic Identification of Babesia Spp in Sheep in Mosul City - Eman . Suleiman; Baydaa Al-lahaibi (Basrah Journal of Veterinary Research)
The Babesia is one of the most important parasites transmitted by hard ticks and is responsible for high infection and mortality rates in sheep herds in various countries of the world. The current study included the diagnosis of the Babesia parasite in 260 blood samples collected from sheep from different areas of the city of Mosul. Thin blood smears were prepared from them, stained with the Giemsa stain, and examined by using the light microscope. The Babesia species was diagnosed in 112 blood samples, with a total infection rate of 43.07%. Two species of Babesia were diagnosed: The large-sized Babesia (Babesia motasi) with a measurement rate of (3.76±0.83) x (2.39±0.78) and a range of (2.5-5) x (1-5) microns and small sized Babesia (Babesia ovis) with a measurement rate of 1.81±0.58 x (1.1±0.47) microns, with a range of (1-2.5) x (1.1-2.1) microns. The current study also included the possibility of using the fluorescent Acridine orange stain (AO) to stain 50 sheep blood samples. This stain was distinguished by its easily and speed in diagnosing infection with the Babesia parasite in blood smears within two minutes. This stain is useful in survey and epidemiological studies, but it is not useful in the specific identification of the parasite